2022
DOI: 10.15244/pjoes/142144
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Gamma Radiation Effect on Functional Traits of <i>Tradescantia Flumnensis</i> L.

Abstract: The effect of radioactivity on the environment, especially on plants, has always been one of the vital researches of radio-ecology. However, long-term irradiated ecosystems are very rare. Occasionally, one special miniature ecological environment object consisted of thorium mineral (Th-232) and Tradescantia flumnensis L. over 10 years is carried out to evaluate the effect of long-term low-radioactivity gamma radiation on herbaceous plant. Several functional features of Tradescantia flumnensis L. are selected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We found that LiP activity has significant positive correlations with radiation intensity, C/N ratio, C%, N%, and abundance of Ectomycorrhizal fungi and Rhizobiales, and plant δ 15 N increase with increasing radiation intensity, which is consistent with the hypothesis of the “symbiotic microbial effect.” In addition, the symbiotic microbial effect can also explain some physiological changes in plants to adapt to long-term ionizing radiation. For example, the plants in the low group improve their damaged nutritional status due to radiation by enhancing the nutrient absorption ability of the root system, which makes the specific root length of the plants in the low group significantly lower than that of the blank group, while the root dry matter proportion is significantly higher than that of the blank group ( Li et al, 2022 ). Moreover, the abundance of Ectomycorrhizal fungi in the high group is 6 times that of the medium group, 13 times that of the low group, and 0 in the blank group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that LiP activity has significant positive correlations with radiation intensity, C/N ratio, C%, N%, and abundance of Ectomycorrhizal fungi and Rhizobiales, and plant δ 15 N increase with increasing radiation intensity, which is consistent with the hypothesis of the “symbiotic microbial effect.” In addition, the symbiotic microbial effect can also explain some physiological changes in plants to adapt to long-term ionizing radiation. For example, the plants in the low group improve their damaged nutritional status due to radiation by enhancing the nutrient absorption ability of the root system, which makes the specific root length of the plants in the low group significantly lower than that of the blank group, while the root dry matter proportion is significantly higher than that of the blank group ( Li et al, 2022 ). Moreover, the abundance of Ectomycorrhizal fungi in the high group is 6 times that of the medium group, 13 times that of the low group, and 0 in the blank group.…”
Section: Discussionmentioning
confidence: 99%
“…In order to cope with the adverse effects of the radiation environment, plants under different radiation intensities have made adaptive changes to the varying radiation intensity, such as reducing specific leaf area, increasing leaf thickness, and shortening plant length ( Li et al, 2022 ). In this case, the plants do not have excess root exudates to stimulate soil microorganisms for nitrogen mineralization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cheng et al (2023) [ 104 ], ectomycorrhizal fungi in soil irradiated by low-dose 232 Th for more than 10 years were positively correlated with radiation intensity. The hyphae of these fungi wrap around plant root cells and form a biomembrane that not only protects plants from pathogens, chemical pollutants [ 136 , 137 ], and radiation but also helps plants absorb soil nutrients, including nitrogen and phosphorus [ 138 ]. Therefore, it is quite conceivable that the growth and defense system of plants are influenced by increasing or decreasing the abundance of plant-associated microbes or the emergence of more toxic pathogens in Chernobyl and Fukushima.…”
Section: Plant-associated Microbesmentioning
confidence: 99%
“…Additionally, ectomycorrhizal fungi can help plants absorb soil nutrients, such as nitrogen and phosphorus (Liu et al, 2022), and are beneficial for carbon fixation (Zak et al, 2019). Thus, ectomycorrhizal fungi improve the nutritional status of plants damaged by radiation (Li et al, 2022), increase the soil C/N ratio, and change the soil microbial diversity and community composition (Zheng and Song, 2022). However, more research is needed to prove that ectomycorrhizal fungi have the function of resisting radiation.…”
Section: Effect Of Gamma Radiation On Soil Microbial Communitymentioning
confidence: 99%